Penggunaan Media Sosial Sebagai Faktor yang Mempengaruhi Self-Esteem Remaja di MA Darul Ulum Palangka Raya - Akbar, Ridho; Surawan Surawan, (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
The advancement of information and communication technology has had a major impact on the dynamics of social change. One of the social media that is currently popular among teenagers is Instagram. This study aims to determine the use of social media as one of the factors that influences self-esteem in teenagers. The methodology used in this study is a literature study, with data sources originating from various scientific journals, articles, websites, and literature reviews that are relevant to the research topic. The results of the study show that the use of social media has a significant impact on shaping adolescent self-esteem.